VALIDITY AND PRACTICALITY OF STUDENTS WORKSHEETS IN DISASTER MITIGATION THROUGH ROLE-PLAYING METHOD TO TRAIN DISASTER MANAGEMENT - Kusumawati, Irene Mira; Fauziah, An Nuril Maulida (PENSA E-JURNAL: PENDIDIKAN SAINS, 2020)
This study aims to describe the development of disaster mitigation students worksheets through the role playing method to train disaster management as well as the validity and practicality of the worksheets. This research was conducted based on the ADDIE development model with class VII K students in the 2019/2020 school year SMPN 21 Surabaya as research subjects. The research data was obtained through observation, interviews, and expert validation methods. The results of the validation assessment found that LKPD of disaster mitigation through role playing methods to train disaster management get very valid results where the content suitability aspect gets a mode 4 value, the presentation suitability aspect gets a mode 4 value, the language suitability aspect gets a mode 3 value, and the suitability aspect the learning method gets mode value 4. The results of the practicality assessment are based on the percentage of learning accomplishments and students activity where at the first meeting the value is 92.8% and the second meeting is 96.8% also the students activitiy reaches an overall average of all phasesis 92,3%. So that the disaster mitigation LKPD through role playing methods to train disaster management is considered very practical for applied during learning. Keywords: validity, practicality, role playing